2011
DOI: 10.1210/me.2011-0081
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Receptor TR3 Enhances p53 Transactivation and Represses DNA Double-Strand Break Repair in Hepatoma Cells under Ionizing Radiation

Abstract: In response to ionizing radiation (IR)-induced DNA double-strand breaks (DSB), cells elicit an evolutionarily conserved checkpoint response that induces cell cycle arrest and either DNA repair or apoptosis, thereby maintaining genomic stability. DNA-dependent protein kinase (DNA-PK) is a central enzyme involved in DSB repair for mammalian cells that comprises a DNA-PK catalytic subunit and the Ku protein, which act as regulatory elements. DNA-PK also functions as a signaling molecule to selectively regulate p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Since NR4A receptors is induced by nutrients [22,83,84] and improve mitochondrial function [30,32], we also expected that these receptors should mediate mitohormesis, an adaptative response to mitochondrial stress that promotes longevity [85,86]. However one study reported that NR4A1 represses DNA repair in hepatoma cells under ionizing irradiation [87]. NR4A1 is also involved in fatty acid cytotoxic activity in b islets pancreatic cells [88].…”
Section: Discussionmentioning
confidence: 99%
“…Since NR4A receptors is induced by nutrients [22,83,84] and improve mitochondrial function [30,32], we also expected that these receptors should mediate mitohormesis, an adaptative response to mitochondrial stress that promotes longevity [85,86]. However one study reported that NR4A1 represses DNA repair in hepatoma cells under ionizing irradiation [87]. NR4A1 is also involved in fatty acid cytotoxic activity in b islets pancreatic cells [88].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest a pro-cell-survival role for NR4As by regulating DNA repair. Conversely, a role for NR4A1 in inhibition of DNA repair has been described in hepatocellular carcinoma cell lines (20).…”
Section: Dna Repairmentioning
confidence: 99%
“…The DNA repair effect of NR4A receptors may contribute to resistance to radiotherapy or chemotherapy (e.g., bleomycin; refs. 18,20). Manipulation of NR4A/DSB binding may be a strategy to increase tumor sensitivity to chemoradiotherapy.…”
Section: Nr4a Receptors: Identified Roles In Human Cancermentioning
confidence: 99%
“…While knockout NR4A1 resulted in reduced p53 expression, therefore, NR4A1 might indirectly modulate the expression of SREBP‐1c via p53, then hinder excess fat accumulation in adipocytes 18, 19. It has been reported that NR4A1 could either enhance DNA‐dependent protein kinase to increase p53 transcription activity 36 or to cause mouse 3T3 cell double minute 2 (MDM2) to separation from p53, thus to protect p53 from MDM2‐mediated ubiquitination and degradation 37. Herein we confirmed the presence of p53 in adipose tissue and found that p53 expression was reduced in adipose tissues of KO mice compared to WT.…”
Section: Discussionmentioning
confidence: 99%